INDEXICALITY OF RELIGIOUS IDENTITY IN YALE MSA E-COMMUNICATION - Aris Munandar (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
Muslims in the U.S is a minority group, thus, vulnerable to discrimation. Yale Muslim Students Association (Yale MSA) as a Muslim community on Campus provides Yale students with the opportunity to come together in a supportive Muslim environment and seeks to educate the Yale and New Haven communities about Islam (YaleMSA.org). This article discusses how Yale MSA indexes Muslim identity in its emails and webpage communication and how the indexicality shows Yale MSA as an empowered Muslim community on campus. It applies the framework for identity analysis proposed by Bucholtz and Hall (2005), especially principle (3) identities may be linguistically indexed through labels, implicatures, stances, styles, or linguistic structures and systems. The analysis of Yale MSA in-group e-mail communication (Yale MSA@gmail.com) and in out-group webpage communication (YaleMSA.org) during the 2008-2014 periods reveals that Yale MSA uses Arabic borrowings and expressions presupposing Muslim life to index’s its Muslim identity. The intensive use of Arabic borrowings in the in-group communication heightens the Islamic atmosphere and strengthens solidarity among members, while the use of Arabic borrowings in combination with English equivalent in out-group communication mitigates prejudice from different faith groups. The choice of overt labels “Muslim” and “non Muslim” rather than “Moslem” and “nonbeliever” implies Yale MSA’s freedom to speak its own voice, and advocate for equal respect among different faith groups in Yale campus and New Haven community. The confidence in speaking its own voice and asserting an equal stance demonstrates that Yale MSA is an empowered Muslim community.